Mantra Berkebun pada Masyarakat Muna Desa Kotano Wuna Kecamatan Tongkuno Kabupaten Muna - La Ode Tarsani; Rahmat Sewa Suraya; Shinta Arjunita Saputri (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2024)
Mantra is one of the local knowledge by the Muna community of Kotano WunaVillage which still exists today and is still often practiced by the muan community for the plantation process. This study aims to 1) find out what spells are used in the gardening process in the Muna community, Kotano WunaVillage, Tongkuno District, Muna Regency; 2) find out the functions contained in the gardening spell in the Muna community, Kotano WunaVillage, Tongkuno District, Muna Regency. In this study, Bronislaw Malinowski's Functionalism theory was used. The type of research was descriptive qualitative, with data collection techniques carried out by observation, interviews and documentation and then analyzed by data reduction, data presentation, and data verification. The results of this study show that there are 7 spells for gardening in the Muna community, namely the Kaebhelaiha Karumbu mantra, the Tughori Mantra, the Kaebelaiha Ghala Mantra, the Kaefemataiha Mantra, the Deala Pasele Mantra, the Deala Kahitela Moghuri Mantra, and the Kasaraka Mantra. The function of the gardening spell in the Muna community is to repel pests and repel supernatural creatures (demons).